Two Oncoviruses of HPV and EBV in Breast Cancer: An Iran-based Study - Fani, Mona; Sadooni, Riam; Haghighat Nejad, Mahmoud; Naseri Mirzavieh, Neda; Mobarak, Sara; Pakzad, Reza; Erfani, Yousef; Salmanzadeh, Shokrollah; Abbasi, Samaneh (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To answer the question of whether viral infections such as Human papillomavirus (HPV) and Epstein-Barr virus (EBV) are involved in the occurrence of breast cancer or not. METHODOLOGY: In this case-control study, 50 paraffin-embedded breast samples (FFPE) and 50 non-cancerous FFPE samples were prepared from patients referred to Abadan hospitals from 2018 to 2021 to identify the genome of HPV and EBV by polymerase chain reaction (PCR). Data were analyzed using SPSS 15 with P-values of 0.05. Confirmed breast cancer biopsy samples with no medical history of chemotherapy and/or radiotherapy, the patient not being pregnant at the time of sampling, not using anti-cancer treatments, and not suffering from systemic inflammatory diseases such as rheumatoid arthritis. Patients of any age, with any breast cancer, and any size or stage of tumor were included without restrictions. RESULTS: Using PCR, HPV DNA was detected in 7/50 (14%) and 2/50(4%) of breast cancers and normal control, respectively. Moreover, 71.42% and 28.57% of HPV-infected persons in the patient’s group were genotypes 16 and 18, respectively. All HPV-infected people in the control group were low-risk genotypes 26 and 53. Also, EBV DNA was found in 2/50 (4%) and 6/50 (12%) of breast cancers and control samples, respectively. Co-infection was not detected in samples. CONCLUSION: Although our study does not provide substantial Evidence about the role of viral infection in the progressiveness of breast tumors, significant studies have shown the critical role of these infections in the progression of breast tumors.